CHALLENGES AND OPPORTUNITIES FOR EARLY CHILDHOOD DISTANCE LEARNING DURING THE COVID-19 PANDEMIC - Rachmadanty, Nofriska (Proceeding International Seminar of Islamic Studies, 2023)
Education continues even during the pandemic. Students learn from home, and the challenge for teachers in preparing learning by using existing opportunities. The purpose of this study is what is the role of schools, parents, and the community in facing the challenges and opportunities of distance learning during the Covid-19 pandemic? This research uses a qualitative approach with a literature study methodology. The technique of collecting data is through book literature and relevant research results, with the instrument being the researcher himself (human instrument). The research analysis used inductive analysis. The result is that teachers develop their potential, learn a lot to master IT in order to innovate. Parents, apart from being second teachers, also supervise, prepare children's learning facilities, assist, and at the same time can communicate intensively between parents and children. Furthermore, the role of the community is to provide internet services for the smooth use of platforms that can be accessed, studied independently or through webinars and workshops.